Recent Utilization of Pediatric Extrapolation and Modeling and Simulation Approaches in Pediatric Drug Development in Japan. - Nakashima, Akinori; Tsujimoto, Akihide; Saito, Masako; Takeda, Jun; Natori, Makiko; Shoji, Satoshi (Journal of Clinical Pharmacology, 2025)
In Japan, the percentage of approved drugs with pediatric indications increased to 30% in 2010‐2015, but no further increase was observed through 2020. The Ministry of Health, Labor, and Welfare in Japan presented draft future directions to promote pediatric drug development, where the modeling and simulation (M&S) approach was introduced as a tool to support efficacy and safety, utilizing existing data when building a flexible data package for pediatric drug approval. M&S is considered a powerful scientific tool in pediatric drug development using the pediatric extrapolation approach. We examined approval application data packages for pediatric drugs approved in Japan from January 2019 to March 2023, where 95 drug products were identified as pediatric drugs for this survey. Drugs with complete, partial, or no extrapolation accounted for 43.2%, 30.5%, and 26.3% of the total drugs, respectively. M&S was widely used as the major rationale in dose selection for pediatric clinical trials and/or the recommended dosing regimen in drug approval applications for the pediatric population (60.0%). Further use of existing data with extrapolation strategies may lead to the development of flexible and efficient data packages for pediatric drug approval. Since safety profiles may be different between pediatric and adult populations due to age‐related factors, pediatric developmental safety should be incorporated into M&S in future assessments. The pharmaceutical industry, regulatory authorities, and academia need to discuss development strategies from an early stage and share lessons learned, thereby facilitating further discussions on efficient pediatric drug development and delivering drugs for children without delay in Japan.